1999
DOI: 10.1007/s002770050549
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine as salvage treatment for refractory thrombotic thrombocytopenic purpura

Abstract: Vincristine (1.4 mg/m(2) on day 1, followed by 1 mg on days 4 and 7) was given to eight patients with thrombotic thrombocytopenic purpura (TTP) who were refractory to plasma exchange (n=4) or plasma infusion (n=4). Seven of eight patients (87%) achieved a complete response; one was refractory to treatment and died within a few weeks. After a median follow-up of 50 months, all responding patients are alive and well. Two patients relapsed and were successfully retreated with vincristine. Toxicity was mild, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 12 publications
1
33
0
1
Order By: Relevance
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
“…Successful vincristine use has been described in various small studies and case reports, usually as a rescue therapy in refractory TTP [17,[24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61] The side-effect profile includes mild peripheral paresthesias, muscle weakness, paralytic ileus, leukopenia, and transient alopecia. 62 Vincristine may work better when used in the initial treatment of patients with TTP, rather than for treating refractory patients.…”
mentioning
confidence: 99%
“…Durante los últimos años, varios trabajos prospectivos han tenido buenos resultados con su utilización, como terapia inicial y de rescate. En éstos se usó la plasmaféresis más un esquema de vincristina en una dosis inicial que variaba entre 1mg al día y 1,4 mg por m 2 , seguido por 3 dosis de 1 mg cada una día por medio 5,9,10,[14][15][16][17] . Diferente a nuestro caso, limitado por costos.…”
Section: Discussionunclassified